A note on the marker-based watershed method for X-ray image segmentation. (April 2017) - Lu, Siyuan; Wang, Shuihua; Zhang, Yudong
Abstract: Background and Objective: A relatively new marker-based watershed method was proposed with international readership circulation. In this letter, we put forward a note on the use of max and min symbols in their study. Methods: We deduced the mathematical equations in their study. Results: We found the ``min'' operation should be changed to ``max'' in original Eqs. (1) and (5). Conclusions: In spite of the two minor problems, the paper contains many important academic points.